Morphological diversity in persimmon fruits (Diospyros kaki) assessed with UPOV descriptors and Tomato Analyzer software - Vendrell, Mario; Blasco, Manuel; Gil-Muñoz, Francisco; Badenes, María L. (2021)
CANSO and the IVIA started a breeding program aimed to increase the available number of commercial varieties adapted to the climatological conditions of the Mediterranean basin, since 96% of the persimmon production in Valencia belongs to the Rojo Brillante variety. First step to design a breeding program is the study of the available plant material and the relationships among them. Although molecular markers are of great utility for studying the relationships among persimmon varieties (Naval et al., 2010), morphological characterization is essential to define the characteristics of the accessions for their protection and registration (Spataro and Negri, 2013; Hurtado et al. 2014). In this respect, persimmon characterization has usually been performed with conventional highly heritable morphological descriptors based on seedling, plant, inflorescence, flower, fruit, and agronomic traits (UPOV2011). These descriptors are very useful for description of varieties but have some limitations, especially when characteristics used for establishing cultivar groups correspond to subtle differences in fruit morphology (Scott 2010). In these cases, conventional descriptors may need to be complemented with more precise characterization tools, as Tomato Analyzer software. This new phenomic tool provides multiple morphology data from scanned images.